Pengaruh Personal Selling Terhadap Keputusan Konsumen Memilih Asuransi Kendaraan - Achmad Tarmizi; Agung Solihin (Prisani Cendekia, 2023)
The aim of this study is to examine the implementation of personal selling policies in vehicle insurance at PT. Tata Wahana Insurance and determine if it affects the consumer's decision to select vehicle insurance at PT. Tata Wahana Insurance. The research employs descriptive and associative research methods. The findings reveal that the personal selling policy for vehicle insurance at PT. Wahana Tata Insurance's uses three methods: Executive Personnel Selling, Inside Personnel Selling, and Outside Personnel Selling. The correlation coefficient analysis indicates a moderate positive relationship between personal selling costs and consumer decisions when selecting vehicle insurance, with a correlation analysis (r) of 0.6. The coefficient of determination shows that the personal selling cost variable (X) contributes to 36% of the consumer decision variable in selecting vehicle insurance (Y), while the remaining 64% is influenced by other factors not included in this study.